Potential roles of gut microbial tryptophan metabolites in the complex pathogenesis of acne vulgaris - Huang, Yukun; Liu, Lu; Hao, Zhenyu; Chen, Lingna; Yang, Qian; Xiong, Xia; Deng, Yongqiong (Frontiers in Microbiology, 2022)
Acne vulgaris is a chronic inflammatory skin disease in which the influence of gut microbiota has been implicated but without clarification of mechanisms. Gut microbiota may exert such an influence via metabolites, particularly those of tryptophan. End metabolites of tryptophan activate receptors, including aryl hydrocarbon, G protein-coupled, and pregnane X receptors to stabilize the immune microenvironment and intestinal mucosal homeostasis. Any impact on the pathogenesis of acne vulgaris remains unclear. The current review collates recent advances concerning potential roles of tryptophan metabolism in mediating skin inflammation, follicular sebaceous gland function and intestinal permeability, all of which influence the pathogenesis of acne vulgaris. The aim was to improve understanding of the pathogenesis of acne vulgaris and to expose therapeutic opportunities.